Isolation and Structure Elucidation of Soulatro Coumarin From Stem Bark of Calophyllum soulattri Burm F and In Vivo Antiplasmodial Activity by Using Mice Infected by Plasmodium berghei - Abbas, Jamilah; Darmawan, Achmad; Syafruddin, . (Indonesian Research Gateway, 2011)
The soulatro coumarin compound was isolated and elucidated from the stem bark of Calophyllum soulattri Burm F, the samples were collected from Jayapura Papua Irian Island inÃÂ Indonesia.ÃÂ IsolationÃÂ processÃÂ wasÃÂ doneÃÂ byÃÂ macerationÃÂ atÃÂ roomÃÂ temperatureÃÂ inÃÂ methanol, thanÃÂ partitionedÃÂ inÃÂ aÃÂ mixtureÃÂ ofÃÂ nÃÂ hexane-waterÃÂ (1:1),ÃÂ followedÃÂ byÃÂ dichloromethane-water (1:1)ÃÂ ÃÂ ÃÂ andÃÂ ethylÃÂ acetate-waterÃÂ (1:1).ÃÂ AÃÂ portionÃÂ ofÃÂ ethylÃÂ acetateÃÂ extractÃÂ wasÃÂ subjectedÃÂ to column chromatography over silica gel packed and eluted with n-hexane a gradient of ethyl acetate to 100% followed by CHCl3ÃÂ in MeOH (20:1, 10 :1, 5:1, 1:1). FractionÃÂ B (CHCl3 in MeOH 20:1) was subjected to column chromatographyÃÂ over silica gel 300 meshÃÂ and eluted withÃÂ EtOAc-MeOHÃÂ mixturesÃÂ ofÃÂ increasingÃÂ polarity.ÃÂ FactionÃÂ withÃÂ theÃÂ sameÃÂ RfÃÂ valeusÃÂ were combinedÃÂ andÃÂ elutedÃÂ withÃÂ EtOAc-MeOHÃÂ ÃÂ ÃÂ (19:1)ÃÂ showedÃÂ oneÃÂ spotÃÂ onÃÂ TLC.ÃÂ TheyÃÂ were combinedÃÂ andÃÂ evaporatedÃÂ toÃÂ yieldÃÂ aÃÂ solidÃÂ thanÃÂ wasÃÂ recrystallizedÃÂ inÃÂ mixtureÃÂ ofÃÂ CH2Cl2-methanolÃÂ toÃÂ giveÃÂ soulatroÃÂ coumarinÃÂ compound.ÃÂ TheÃÂ structureÃÂ wasÃÂ determinatedÃÂ by spectroscopic analysis, in particular by 1D and 2D NMR techniques, from these spectra data conclutionÃÂ thatÃÂ compoundÃÂ isÃÂ soulatroÃÂ coumarin.ÃÂ AntimalarialÃÂ assayÃÂ wasÃÂ testedÃÂ against Plasmodium berghei parasite as in vivo using 18 mices rodent wich was infected byÃÂ Plasmodium bergheiÃÂ parasite.ÃÂ TheÃÂ soulatroÃÂ coumarinÃÂ ÃÂ ÃÂ showedÃÂ activityÃÂ againstÃÂ P.ÃÂ bergheiÃÂ withÃÂ dosage 0.0005867ÃÂ mM/1ÃÂ kgÃÂ bodyÃÂ weightÃÂ ;ÃÂ 0.005867ÃÂ mM/1ÃÂ kgÃÂ bw;ÃÂ 0.05867ÃÂ mM/1ÃÂ kgÃÂ bw;ÃÂ 0.5867 mM/1ÃÂ kgÃÂ bwÃÂ 5.867ÃÂ mM/1ÃÂ kgÃÂ bwÃÂ andÃÂ 58.67ÃÂ mM/1ÃÂ kgÃÂ bwÃÂ couldÃÂ inhibiteÃÂ growthÃÂ rateÃÂ of parasite = 57.32%; 63.37%; 43.02%; 53.49%; 47.67% respectively. ÃÂ Keywords : Antiplasmodial activity, coumarin, Calophyllum soulattri Burm. F, in vivo,ÃÂ Chloroquine, Plasmodium berghei.